Nutraceuticals in Acute and Prophylactic Treatment of Migraine - Daniel, Oved; Mauskop, Alexander (Current treatment options in neurology, 2016)
Opinion statement People who suffer from headaches often prefer nutraceutical treatment over traditional pharmacological approaches, due to fear of possible side effects, drug dependence, or addiction. Since treatment with nutraceuticals does not require a doctor’s prescription, many patients rely on their own judgment as to when and which one to take, often without consultation or guidance from their physician. Some physicians could provide information about potential efficacy and side effects of various products, but many are not familiar with the nutraceuticals. Widespread skepticism persists among doctors about the effectiveness of these treatments. This is largely due to the lack of rigorous clinical studies. However, even when incontrovertible scientific evidence exists, many physicians remain distrustful of the evidence. The following review summarizes randomized controlled trials of some of the most commonly used non-pharmacological treatments, including magnesium, coenzyme Q 10 , riboflavin (vitamin B2), petasites, and feverfew (Table 1 ).